A 100-m Sprint Time Is Associated With Deep Trunk Muscle Thickness in Collegiate Male Sprinters - Fujita, Shimpei; Kusano, Seiya; Sugiura, Yusaku; Sakuraba, Keishoku; Kubota, Atsushi; Sakuma, Kazuhiko; Suzuki, Yoshio; Hayamizu, Kohsuke; Aoki, Yuma; Sugita, Masaaki (Frontiers in Sports and Active Living, 2019)
Introduction One reason athletes train their trunk muscles is that body trunk stability has been shown to prevent injury. However, the relationship between body trunk muscle thickness, particularly that of deep muscles, and athletic performance remains to be clarified. Purpose We aimed to explore the relationship between 100-m sprint performance and the sizes of the trunk stabilizing muscles—the psoas major muscle (PM), transversus abdominis (TA), and multifidus muscle (MM) in collegiate sprinters. Methods Fourteen male sprinters belonging to a university athletics club participated in this study. The thicknesses of the TA and MM were measured using an ultrasonic diagnostic apparatus (ProSound C3; Aloka, Tokyo, Japan). The cross-sectional area of the PM was assessed by a magnetic resonance imaging apparatus (Vantage Elan; Toshiba Medical Systems, Tokyo, Japan). The relationship between these anthropometric parameters and the 100-m sprint time was analyzed by Spearman's correlation coefficient, multi- regression analysis, and the change-point regression model. Results The sizes (mean ± SD) of the muscles were: PM, 43.074 ± 7.35 cm2; TA, 4.36 ± 0.72 mm; and MM, 3.99 ± 0.48 cm. The mean 100-m sprint time was 11.00 ± 0.48 s. Spearman's correlation analysis revealed that the 100-m sprint time had a significant moderate negative correlation with TA (ρ = −0.691, p < 0.01) and a low negative but not significant correlation with MM (ρ = −0.327, p = 0.28), whereas PM did not show a significant or in-negligible correlation. The change-point regression model found the change-points in the 100-m sprint time and the thickness of the TA and MM at 4.70 mm (95% CI: 4.00–5.43 mm) and 3.84 cm (95% CI: 3.28–4.31 cm), respectively. The sprint time decreased with an increase in the thickness of the muscles up to the change-points, whereas it did not change even if the muscles got thicker than the change-points. The change-points were consistently observed when the thickness of the muscles were normalized by body mass. Conclusion Sprint performance for 100-m was found to be associated with TA and MM thickness in a biphasic manner. As muscle thickness increased, the sprint time decreased, followed by a plateau phase.